Pengaruh Penerapan Akuntansi Biaya dan Sistem Pengendalian Internal terhadap Kinerja Keuangan UMKM dengan Komitmen Manajemen sebagai Variabel Moderasi di Kabupaten Sumbawa - Sriyatun; Sugiarto, Aris (SENTRI: Jurnal Riset Ilmiah, 2025)
This study examines the effect of cost accounting implementation and internal control systems on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) with management commitment as a moderating variable in Sumbawa Regency. Grounded in contingency theory and agency theory, this research employs a quantitative explanatory cross-sectional design using Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS 4. Data were collected from 100 MSME owners/managers through structured questionnaires based on Slovin's formula from a population of 1,359 MSMEs. The measurement model confirmed convergent validity (AVE > 0.50), discriminant validity (HTMT < 0.90), and internal consistency (Cronbach's alpha > 0.85). Structural model assessment with 5,000 bootstrap subsamples reveals that cost accounting implementation significantly and positively affects MSME financial performance (β = 0.387; p < 0.001), and internal control systems exert a positive and significant influence on financial performance (β = 0.342; p < 0.001). Crucially, management commitment significantly moderates both relationships: it strengthens the effect of cost accounting on financial performance (β = 0.198; p = 0.004) and amplifies the impact of internal control systems on financial performance (β = 0.167; p = 0.012). The model explains 63.8% of the variance in financial performance (R² = 0.638) with strong predictive relevance (Q²predict = 0.597). These findings underscore the necessity of integrating formal accounting practices and internal controls with strong managerial commitment to optimize MSME financial outcomes in emerging regional economies.